CO2 separation through carbon tubular membranes: effect of polymer composition - Sazali, N.; W. Salleh, W.N.; Ismail, A.F.; M. Nordin, N.A.H.; Harun, Zawati (Avestia Publishing, 2016)
Carbon membrane can be regarded as the future of the separation media in gas separation process due to its high gas separation performance, ease process ability, and moderate energy requirement as compared to conventional separation. In this study, the influence of the polymer (Matrimid 5218) composition; 5wt%, 10wt%, 13wt%, 15wt%, and 18wt%, on the gas permeation properties was investigated. The supported polymer precursor was prepared by coated the polymer solution on TiO2 –ZrO2 tubes by using dip-coating method before undergoes carbonization at 850°C under Nitrogen atmosphere. Pure gas permeation tests were performed by using CH4, and CO2, at room temperature and pressure of 8 bars. It was found that polymer composition plays a significant role in the carbon membrane preparation. The highest CO2/CH4 selectivity of 83.30 was obtained for carbon membrane prepared from 15wt% polymer composition.